Carbon Fiber Composites: A Solution for Light Weight Dynamic Components of AFVs - Nirala, Subodh Kumar; Shankar, Sarath; Sathishkumar, Dhanalakshmi; Kavivalluvan, V.; Sivakumar, P. (Defence Science Journal, 2017)
Changing circumstances across the world require armored fighting vehicle (AFV) of a country to be more agile, easily manoeuverable and transportable besides other key requirements like firepower and protection. Therefore, the AFV should be as light as possible. The use of conventional materials and techniques do not fulfill the requirement of light weight AFV. The composite materials having high specific modulus, specific strength and directional properties are the alternative substitution for reducing the weight. A customized design approach with proper selection of composite material is essential to make AFV components with required properties at lower weight as compared to the traditional approach. Special properties like resistance to moisture, solvents, UV degradation etc. could be imparted to the composite components by the use of proper additives or fillers. This paper deals with the development of dynamic members like road wheel, top roller and axle arm, whose count is always more in any AFVs, using carbon-epoxy composite material. The details of composite materials used and the manufacturing processes adopted are briefly discussed. The static load test carried out to assess the structural integrity as well as non-destructive tests (NDT) performed to detect the defects are also dealt in detail. Preliminary Finite Element Analysis and Multi-body Dynamic Analysis have also been discussed. These analyses have been done mainly to understand the sustainability and performance of the components developed under the given loading conditions.